Values for Inclusion of Children with Disability in Mainstream Education - Bhattarai, Tikaram (GS WOW: Wisdom of Worthy Research Journal, 2024)
This study aims to identify and explore the values that extend the inclusion of differently able children for mainstreaming in the general education with focus to the significance of changing trend of values. Values for inclusion of children with disability are crucial especially to plugging special education to the general one. The study is based on review and perception of interviewer. Key findings highlight the importance of diversity, fairness, collaboration, and empowerment as important values using efforts closer to inclusive schooling. The inclusion of children with impairments in mainstream school is contingent upon the fulfillment of numerous fundamental ideals, as this study has identified. Diversity, equity, collaboration, and empowerment were constantly emphasized as essential values in the interviews with educators, parents, and officials. Educator emphasized the importance of professional development and educational justice. Parents stressed the value of their children learning along with classmates and the non-discrimination policy. The importance of healthy policies, allocation of sufficient financing, and an inclusive curriculum was emphasized by policymakers. Each and every stakeholder group also considered respect and empathy to be essential.